FOOD SYSTEM DETERMINANTS INFLUENCING THE SUCCESS OF IRON FORTIFICATION PROGRAMS AMONG CHILDREN IN SOUTHEAST ASIA: A SYSTEMATIC REVIEW - Refani Alycia Kusuma; Heru Komarudin; Roma Yuliana (PT. Varians Statistik Kesehatan, 2026)
Background: Iron deficiency and anemia remain major public health challenges among children in Southeast Asia, contributing to impaired growth, cognitive development, and long-term health outcomes. Although iron fortification has been widely implemented, program effectiveness has remained inconsistent across the region. This systematic review aimed to examine food system determinants influencing the success of iron fortification programs among children in Southeast Asia and their implications for Indonesia. Methods: A systematic review was conducted following the PRISMA 2020 guidelines. Literature searches were performed using PubMed/MEDLINE and Scopus. Studies published between 2015 and 2026 were screened for eligibility. Quantitative, qualitative, mixed-methods, and implementation studies evaluating iron fortification interventions among children in Southeast Asia were included. Data were synthesized narratively using a food systems perspective. Results: Nine studies were included, primarily randomized controlled trials and community-based interventions conducted in Cambodia and Indonesia. Iron fortification interventions, particularly fortified rice delivered through school feeding programs, generally improved hemoglobin levels, micronutrient status, and cognitive outcomes. However, intervention effectiveness was influenced by adherence, cultural acceptability, caregiver practices, inflammation, gut health, and implementation sustainability. Conclusions: The success of iron fortification programs was influenced not only by nutrient delivery but also by broader food system determinants. Integrated food systems approaches were considered essential to improve child nutrition outcomes in Southeast Asia, particularly in Indonesia.